The Dynamics of Human Rights Diplomacy in Asean - Myajaya, Roby Arman; Hanifah, Hana; Sari, Wulan; Jamilah, Mariam; Gloria, Nuvola; Aliyah, Putri (International Journal of Education, Information Technology, and Others, 2024)
This article discusses developments and challenges in human rights diplomacy in ASEAN, with an emphasis on policy changes since ASEAN was established in 1967. It analyzes how the principles of non-intervention and sovereignty of member states affect the implementation of human rights, as well as the important role of the ASEAN Intergovernmental Commission on Human Rights (AICHR) established in 2009. Despite progress such as the ASEAN Human Rights Declaration in 2012, ASEAN still faces major challenges in the consistent implementation of human rights. Case studies in Myanmar, Thailand, and the Philippines show ASEAN's limitations in responding to human rights violations. This article also reviews the contribution of non-state actors such as NGOs and media in human rights diplomacy, and recommends strategies to strengthen human rights mechanisms in the region. The conclusion of this study is that despite the obstacles, there is potential to improve human rights protection through policy reforms and increased civil society participation.